Digitalization Challenges on Management Decisions During the COVID-19 Pandemic in Romania - Valentin Stoica; Radu Rugiubei (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
Organizations with pre-existing digital infrastructures navigated disruptions more effectively, while those lacking digital strategies faced greater challenges in decision-making and workforce coordination. This research looks into the accelerated impact of digitalization on managerial decision-making process during the COVID-19 pandemic in Romania, by conducting 11 interviews with managers from various companies and industries. Results point out that an accelerated adoption rhythm of digital tools was necessary for remote work adaptation, business continuity and operational resilience. The study highlights both opportunities and challenges of digital transformation, emphasizing the need for digital skills development, cybersecurity enhancements, and adaptive crisis management. Many digital changes adopted during the pandemic have become permanent business practices, reshaping long-term strategies. The research underscores the importance of integrating digitalization into strategic planning to ensure business sustainability. Future studies should explore quantitative validations, industry-specific challenges, and the long-term impact of digital transformation beyond the pandemic.